Korelasi Pengalaman Kerja, Kesejahteraan Dengan Motivasi Kerja Guru-Guru SMA Swasta - Umbu Tagela; Herry Sanoto; Mila Chrismawati Paseleng (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
This is a correlational research, aimed to determine (1) the correlation between the work experience and work motivation of private high school teachers in Waingapu City, (2) the correlation between well-being and work motivation of private high school teachers in Waingapu City, and (3) the correlation between the work experience, well-being, and work motivation of the private high school teachers in Waingapu City. The data collection techniques used in this study were observation, documentation, and questionnaire. The research located in private high schools in Waingapu City in 2021 (PGRI High School, Muhammadyah High School, Kristen High School, and Andaluri Catholic High School). The population of this study were 140 people, with the sample of  90 people. The data analysis technique was the bivariate correlation with the Spearman test tool, which was processed using the SPSS Version 21.00. The research results are as follows: (1) There is a significant correlation between the work experience and work motivation because the overall correlation coefficient value (r = 0.442**) is at a 1% confidence level with a Sig. 0.000. (2) There is a significant correlation between well-being and work motivation of private high school teachers overall (r = 0.469**) at a 1% confidence level with a Sig. 0.000. (3) There is a significant correlation between work experience, well-being, and work motivation, with a correlation coefficient of (r = 0.604**) at a 1% confidence level with a Sig. 0.000. The suggestion is that the school foundation needs to optimize their efforts to improve the teacher work motivation through the appreciation of their work experience and also paying attention to the well-being of the teachers.